small scale beekeeping (2016)
James Salander spoke to third grade students from C.W. Harris Elementary School about hives, taking care of bees, and honey production. He invited the students to explore the clothing, equipment and "packaged" bees in order to understand the process from flowers to honey.
Classification: Agriculture.
Classification: Education.
Classification: Science.